المشاكل الأسرية في جنوب إيران والمناهج المتبعة لحلها: دراسة ميدانية = Family problems in southern Iran and the approaches used to solve them: a field study - Dadkhoda, Somayeh; Amanullah, Muhammad; Mohamed, Hossam El-Din Ibrahim (IIUM Press, 2024)
من أهم أهداف الزواج هو تكوين أسرة آمنة ومستدامة بعيدة عن المشكلات التي قد تواجهها، مع العلم أن هذه المشاكل تختلف من أسرة لأخرى، بما في ذلك الأسر الجنوبية، مما قد يهدد استمرارية الحياة الزوجية. ونظراً لعدم توفر الدراسات المركزة فيها، يهدف هذا البحث إلى دراسة المشاكل الأسرية الجنوبية والمناهج المستخدمة لحلها في تلك المنطقة. وتتمثل أهمية هذا البحث في إجراء دراسات دورية لوضع حلول مبتكرة تناسب احتياجات الأسر في مختلف العصور والثقافات. ويمكن أن يكون هذا المنهج مفيد للمجتمعات الدعوية في الدول الإسلامية أن تحاول الوصول إلى استدامة الأسرة المسلمة باستخدام هذا المنهج. واعتمد البحث على المنهج الاستقرائي، والمنهج التحليلي، والمنهج الميداني، وذلك من خلال قراءة للمصادر والمراجع من الكتب والمقالات والرسائل العلمية واستخراج المصطلحات والمفاهيم ذات الصلة بالموضوع ثم تحليل البيانات والتمييز بين المفاهيم والمصطلحات. وبالتالي اجراء المقابلات مع نشطاء الاجتماعيين وعلماء النفس في جنوب إيران عن المشاكل الأسرية وتدوين الشروح والتفاسير عنهم في سجل خاص للوصول إلى مناهج المتبعة عندهم لحل المشاكل الأسرية في جنوب إيران. وينتج هذا البحث إلى أن المنهج المتبع في جنوب إيران نهج شامل لمعالجة مشاكل الأسرة بشكل جوهري حيث يمتد النهج مدى سنوات معينة بتقديم الدورات، والمؤتمرات، ووروش العمل لتوعية الأزواج حول معلومات اللازمة في الحياة الزوجية لسعادتها والابتعاد عن المشاكل التي تزلزل بناء الأسرة. ***** One of the primary goals of marriage is to establish a secure and sustainable family, free from the problems that may arise. However, these problems vary from one family to another, including among southern Iranian families, which can potentially threaten marital continuity. Given the lack of focused studies in this area, this research aims to explore family issues specific to southern Iran and the methodologies employed to address them in that region. The significance of this study lies in periodically developing innovative solutions that suit the needs of families across different eras and cultures. Such an approach could be found valuable for other Islamic communities striving to achieve family sustainability. The research methodology includes inductive, analytical, and field-based approaches. Sources are reviewed, relevant terms and concepts are extracted, and data is analyzed to distinguish between various ideas and terminology. Additionally, interviews with social activists and psychologists in southern Iran contribute to documenting their approaches for resolving family issues. The findings indicate that the approach followed in southern Iran is comprehensive, addressing family problems fundamentally. It extends over specific years through courses, conferences, and workshops designed to educate couples about essential marital information and help them navigate away from issues that may destabilize family foundations.